Eradication of Helicobacter pylori: challenges and advances - Yousra Sbibih; Abderrazak Saddari; Ilham Alla; Said Ezrari; Elmostapha Benaissa; Yassine Ben Lahlou; Mostafa Elouennass; Adil Maleb (Iranian Journal of Microbiology)
Background and Objectives: Helicobacter pylori, identified in 1982, remains a major cause of gastric infections. Despite extensive research, an ideal treatment regimen for its eradication is yet to be determined, with antibiotic resistance posing a significant challenge. This study, conducted at Mohammed VI University Hospital, aimed to evaluate and compare the effectiveness of different therapeutic protocols for H. pylori eradication. Materials and Methods: This 13-month retrospective descriptive study was conducted at the Microbiology Laboratory of Mohammed VI University Hospital in Oujda, Morocco, to evaluate patients suspected of H. pylori infection using the urea breath test. Results: A total of 190 patients were included, with an overall eradication rate of 73%. Three therapeutic protocols were tested, and bismuth concomitant therapy showed the highest eradication rate at 82%, outperforming the other regimens. Conclusion: These findings highlight the importance of combining antimicrobial agents with antisecretory treatments to enhance eradication outcomes. The study also emphasizes the need for novel treatment strategies, particularly in light of rising antibiotic resistance. Vonoprazan-based regimens appear to offer a promising alternative, especially in the absence of antibiotic sensitivity testing. Future research should focus on optimizing treatment protocols while preserving beneficial gut flora.